2004
DOI: 10.2174/1568007043336743
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-Gated Calcium Channels as Targets for the Treatment of Chronic Pain

Abstract: This review focuses on the importance of voltage-gated calcium channels in modulating and controlling the function of peripheral and central neurons involved in nociceptive processing. We describe the different families of voltage-gated calcium channels that are expressed in pain pathway neurons, how the expression levels of calcium channel currents change in chronic pain conditions, and the validation of N-type, T-type, and P-type calcium channels as targets for the treatment of pain. The molecular mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…There are substantial experimental evidences that argues in favor of the participation of voltage-gated Ca 2+ channels as key elements in the transmission of pain signals (McGivern and McDonough, 2004;Lee et al, 2005;Chung et al, 2008;Zamponi et al, 2009;Perret and Luo, 2009). Knowing that eugenol is related to capsaicin in terms of chemical structure and that capsaicin has been demonstrated to inhibit high voltage-gated Ca 2+ channels (Petersen et al, 1989;Bleakman et al, 1990), these information combined have motivated studies to investigate whether eugenol would interact with high voltage-gated Ca 2+ channels.…”
Section: Constituents Of Essential Oils That Acts In the Central And mentioning
confidence: 99%
“…There are substantial experimental evidences that argues in favor of the participation of voltage-gated Ca 2+ channels as key elements in the transmission of pain signals (McGivern and McDonough, 2004;Lee et al, 2005;Chung et al, 2008;Zamponi et al, 2009;Perret and Luo, 2009). Knowing that eugenol is related to capsaicin in terms of chemical structure and that capsaicin has been demonstrated to inhibit high voltage-gated Ca 2+ channels (Petersen et al, 1989;Bleakman et al, 1990), these information combined have motivated studies to investigate whether eugenol would interact with high voltage-gated Ca 2+ channels.…”
Section: Constituents Of Essential Oils That Acts In the Central And mentioning
confidence: 99%
“…Pharmacology and genetic studies showed that Ca v 2.2 inhibiting activity was an effective way to manage or alleviate symptoms of inflammatory, chronic and neuropathic pain (Kerr et al, 1988; Gohil et al, 1994; Saegusa et al, 2001, 2002; McGivern and McDonough, 2004; McGivern, 2006; Altier et al, 2007; Trang et al, 2015). Ca v 2.2 antagonists have therefore long been considered as potential analgesics (Hazelhoff et al, 1982; Mathela et al, 2005; La et al, 2008; Yamamoto and Takahara, 2009; Pajouhesh et al, 2010; Schmidtkco et al, 2010; Swensen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…39 Protein SUMOylation has been reported to modulate neurotransmitter release 36 perhaps via N-type calcium channels that, in turn, are modulated by CRMP2. In summary, SUMO regulation of CRMP2/CaV2.2 signaling may have important implications for chronic pain because CaV2.2 channels are genetically 40,41 and clinically 28,42,43 validated targets for pain management. Future work will also investigate whether SUMOylation of CRMP2 affects its other functions, as well as how it regulates its other interactions.…”
Section: Discussionmentioning
confidence: 99%